Prevalence and associated factors of mild cognitive impairment among middle‐aged and older adults: Results of the first phase of Ardakan Cohort Study on Aging - Ahmad Delbari; Fatemeh‐Sadat Tabatabaei; Hoomaan Ghasemi; Amirali Azimi; Mohammad Bidkhori; Mohammad Saatchi; Mahshid Foroughan; Elham Hooshmand (Health Science Reports, 2024)
Abstract Background and Aims Data on mild cognitive impairment (MCI) in low‐ to middle‐income countries are still being determined, despite the fact that most future older adults are expected to reside in these regions. This study aimed to investigate the prevalence and associated factors of MCI in Iran. Methods A cross‐sectional study was conducted on 4938 community‐dwelling subjects aged 50 years or above in the first wave of the Ardakan Cohort Study on Aging. MCI was evaluated using the Mini‐Mental State Examination (MMSE) and the Abbreviated Mental Test Score (AMTS) in literate and illiterate individuals. The relationship between factors associated with the odds of MCI was assessed through logistic regression. Results The prevalence of MCI among all participants, the literates and illiterates, was 15.8%, 6.3%, and 36.4%, respectively. It was found that failure to accomplish any of the MMSE or AMTS items was significantly related to MCI (p < 0.001). Age ([odds ratio (OR): 1.05; p < 0.001 in the literates], [OR: 1.06; p < 0.001 in the illiterates]), sex (OR: 0.13; p < 0.001 in the illiterates), history of stroke ([OR: 2.86; p = 0.006 in the literates], [OR: 2.04; p = 0.045 in the illiterates]), and depression ([OR: 1.87; p < 0.001 in the literates], [OR: 1.41; p = 0.008 in the illiterates]) were significantly associated with MCI. Conclusion This study highlights the significant associations between age, education, depression, stroke, and MCI in Iranian participants. These findings emphasize the need for targeted interventions in low‐literacy populations, mental health screening, and stroke prevention strategies to mitigate the burden of MCI and enhance cognitive health.